Improving Reading Comprehension and Vocabulary Knowledge through Cooperative Learning Strategies: A Case of Nursing Students at Zanjan Medical University - Aref Shamsoddin; ali soltani (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Cooperative learning as an educational approach plays a crucial role in English as a second/foreign language education. The effective role of cooperative learning seems to be so dominant that it deserves further investigation. Objectives: This study aimed at investigating the impact of cooperative learning strategies on reading comprehension and vocabulary learning of nursing students in Zanjan University of Medical Sciences. Methods: Seventy eight female nursing students, who were enrolled in two intact classes, constituted the participants of the study. To select participants with equal language proficiency, the researchers administered the Oxford Placement Test. Forty learners whose scores fell between one standard deviation below and above the mean were selected. Then, the researchers used a pre-test to check the participants' reading comprehension and vocabulary knowledge of the participants. The participants were randomly devided into experimental and control groups. The experimental group (n=20) was taught through the cooperative strategies while the control group (n=20) was instructed through conventional methods. After the treatment, a post-test was employed to measure the students' reading comprehension and vocabulary knowledge. The data was analyzed by independent sample t-test using SPSS-16 software. Results: The results of the Independent Samples t-test showed that cooperative strategies have a significant influence on the participantschr('39') reading comprehension and vocabulary knowledge. Conclusion: It was concluded that cooperative learning should be practiced in reading and vocabulary classes as they solve many of the problems students face in traditional settings.